2015
DOI: 10.5539/gjhs.v7n4p110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation and Risk Factors of Tuberculosis Infection in Malaysia:Case Study of a Community Clinic

Abstract: Introduction:The main aim of this study was to describe the clinical manifestation of tuberculosis infection cases in Malaysia and to determine the individual risk factors for their occurrence.Methodology:The study adopted a quantitative research approach with use of descriptive statistical approach. The study setting was a community clinic which treats walk in patients who are mainly living and working in the surrounding areas. The study was conducted for a period of one year. All tuberculosis patients who so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…The present study identified diabetes mellitus as another risk factors for TB, which has also been reported in previous series. 20 Insight into the mechanism underlying this association might be provided by immunological studies. Interferon-gamma, which is crucial for host defense against TB, is expressed at low levels in diabetic mice infected with Mycobacterium tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified diabetes mellitus as another risk factors for TB, which has also been reported in previous series. 20 Insight into the mechanism underlying this association might be provided by immunological studies. Interferon-gamma, which is crucial for host defense against TB, is expressed at low levels in diabetic mice infected with Mycobacterium tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, the current policy to deport foreigners with active TB within a month resulted in poorer treatment success rates [34]. To avoid this problem, a national strategy to re-strategize the distribution of anti-TB treatment in Sabah is required, and treatment monitoring is important to minimise the burden and prevent the spread of TB infection in the state [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk factors for LTBI and active TB such as: sex; age; low socioeconomic status; low level of education; smoking; HIV/TB coinfection; use of alcohol and other drugs; malnutrition; diabetes mellitus; renal failure and other metabolic conditions; use of corticosteroids, other immunosuppressants and chemotherapy; among others. These factors are exacerbated in a confinement environment with overcrowding, poor ventilation and lighting and low hygiene standards such as Brazilian prisons 5 , 7 , 9 , 16 , 17 , 23 , 29 , b , i .…”
Section: Discussionmentioning
confidence: 99%